Factors Influencing the Occurrence of Preeclampsia in Pregnant Women at Sibuhuan Hospital, Barumun District, Regency The Old Field in 2022 - Suhartini (Science Midwifery, 2022)
Preeclampsia is still the biggest cause of maternal and fetal morbidity and mortality worldwide. One of the basic theories that is most responsible for the occurrence of this syndrome is endothelial dysfunction in placentation defects. (Keman, 2014). Maternal mortality in Indonesia is still dominated by the three main causes of death, namely bleeding, preeclampsia and infection. Preeclampsia affects 3-5% of pregnancies and is responsible for more than 60,000 maternal deaths and 500,000 fetal deaths per year worldwide. The purpose of this research is to find outFactors Affecting the occurrence of Pre-eclampsia in pregnant women in hospitals. Sibuhuan Barumun District, Padang Lawas Regency in 2022. The type of research conducted is analytic observational with a case control approach, the population in the study is 733 people and the number of samples is 27 people using the techniquepurposive sampling. The data collected in this study is secondary data, namely data obtained from medical records. The data analysis used was univariate analysis and bivariate analysis. The research results areFactors that do not influence the occurrence of pre-eclampsia are age, parity, spacing of pregnancies, history of diabetes mellitus, and factors that influence the occurrence of pre-eclampsia are factors of history of hypertension in pregnant women in hospitals. Sibuhuan, Barumun District, Padang Lawas Regency in 2022. It is hoped that all health workers inHOSPITAL. Sibuhuanexpected to be more active in providing counseling related tofactors that influence the occurrence of pre-eclampsia in pregnant women